Réponses

2014-09-18T22:49:20+02:00
59)
A = 7 + 5 x 6 - 8 x 9
A = 7 + 30 - 72
A = 37 - 72
A = - 35

B = 6 x (- 3) + 11 - (- 7)
B = - 18 + 11 + 7
B = - 18 + 18
B = 0

C = 2 x (12 - 15) + 9
C = 2 x (- 3) + 9
C = - 6 + 9
C = 3

D = 5 - 8 x (- 7) + 3
D = 5 + 56 + 3
D = 64

60)
A = 8 x (- 4) + 14 : (- 7)
A = - 32 - 2
A = - 34

B = 35 : 5 - (16 - 20) : (- 2)
B = 7 - (- 4) : - 2
B = 7 + 4 : - 2
B = 7 + 2
B = 9

C = 48 : 16 - 6 x (- 5) + 18
C = 3 + 30 + 18
C = 51

61) x = - 5 ; y = 4 ; z = - 2,5

a) x + y + z = - 5 + 4 + (- 2,5) = - 5 + 4 - 2,5 = 4 - 7,5 = - 3,5

b) xyz ) - 5 x 4 x (- 2,5) = - 20 x - 2,5 = 50

c) x - yz = - 5 - 4 x - 2,5 = - 5 + 10 = 5

62) x = 12 ; y = - 6 ; z = - 3

a) xy : z = 12 * - 6 : - 3 = - 72 : - 3 = 24

b) (x + y) : z = (12 + (- 6)) : - 3 = (12 - 6) : - 3 = 6 : - 3 = - 2

c) x : y * (- z) = 12 : - 6 * - - 3 = 12 : - 6 * 3 = - 2 * 3 = - 6